Sharia Bumdes: Opportunities, Challenges and Their Role In Village Sharia Economic Development - Nawawi, Khisom (Robust: Research of Business and Economics Studies, 2024)
Sharia Village-Owned Enterprises (BUMDes) have become the subject of significant attention in economic development in Indonesia. With the majority of the rural population being Muslims, Sharia BUMDes offers great potential for developing an economy based on Islamic principles. This research shows the potential of Sharia BUMDes, as well as the opportunities, challenges they face and their role in developing the village sharia economy. Islamic economic principles such as justice, openness and sustainability are the basis for Sharia BUMDes in advancing the local economy. However, the implementation of this concept is faced with challenges such as a lack of public understanding of Islamic economics and pressure to manage BUMDes professionally. By building strong partnerships with local economic actors and implementing sharia economic principles effectively, Sharia BUMDes have great potential to become a driving force for a sustainable and inclusive economy at the village level.